Förskollärares ledarskap som ett kunskapsfält i behov av begreppsliga resurser i förskoleverksamhet, utbildning och forskning - Madeleine Brodin Olsson; Anne Kultti (Educare)
The present study aims to investigate supervision activities as a form of teaching leadership in preschool teacher education. Work-based education constitutes a particular context for understanding of leadership in preschool due to its intention of bridging between practical and theoretical experience and knowledge. The empirical data analyzed consist of audio-recorded supervision in the form of weekly conversations between the student teacher and the preschool teacher within a five-week course with leadership as the learning content. Theoretically grounded in a sociocultural perspective on learning and communication, the analysis shows how leadership is mediated as a relational practice but without a definition. In addition, the conversations focus on the student teacher’s trajectories of developing leadership. In these conversations, the contents: meanings of leadership and the students’ appropriation of leadership, are blurred. Without an explicit meta-perspective in the conversations, it becomes analytically unclear whether, or to what extent, the participants establish conceptual intersubjectivity. The findings are discussed in relation to work-based education as a context for teaching and learning the prospective occupation. We conclude that theoretical knowledge of preschool teachers’ leadership becomes invisible in supervision without an education offering conceptual resources for this content.